Postavljanje podpore v okviru vključevanja staršev matematikov v matematično izobraževanje njihovih otrok - Antolin, Darja; Lipovec, Alenka (Revija za elementarno izobraževanje, 2013)
Scaffolding as Part of Parental Involvement of Mathematicians in their Children‘s Mathematics Education. This article discusses the importance of parents’ scaffolding skills in supporting and guiding their children’s mathematical development. Usually, parents are not aware of scaffolding when helping their children learn mathematics, and they are not much acquainted with scaffolding techniques. In our qualitative research where narrative approach has been used, we investigated how parents who are mathematicians scaffold their children’s mathematical development. The results provide an in-depth insight into parental involvement of this special group of parents, focusing on their scaffolding practices. Our findings suggest that mathematicians are aware of their child’s level of cognitive development. Furthermore, mathematicians accommodate their mathematical activities to the child’s developmental level in order to encourage his or her mathematical reasoning.